Challenges Encountered by Healthcare Providers in COVID-19 Times: An Exploratory Study. (June 2021) - Sengupta, Mitali; Roy, Arijit; Ganguly, Arnab; Baishya, Kuldeep; Chakrabarti, Satyajit; Mukhopadhyay, Indraneel
Healthcare establishments are unique and complex. The Indian healthcare system comprises of public and private healthcare establishments. Different challenges are encountered by the healthcare professionals in their daily operations. The sudden emergence of COVID-19 posed a new threat to the already burdened healthcare system. The pandemic changed the healthcare paradox with newer workplace and societal challenges faced by the healthcare personnel. The purpose of this study is to identify the antecedents of workplace and societal challenges faced by the healthcare personnel. Our study conducted in Kolkata and other adjoining areas of West Bengal included respondents who volunteered for individual in-depth interviews. The sample size was kept at n = 20 after due technical considerations. Freelisting and pile sorting was done to generate clusters. The qualitative study identified five constructs with 18 items under workplace challenges and three constructs with five items under societal/community challenges. Workplace challenges included resource availability, adequacy and allocation, financial issues, perceived managerial ineffectiveness, inconsistent guidelines and perceived occupational stress, while societal/community challenges included dread disease, social adaptiveness and challenges related to essential services. A salience threshold was established and the multidimensional scaling provided four major clusters: financial support and sustainability, adaptive resilience, infection risk mitigation and healthcare facility preparedness. Suggestive actions for the identified challenges were summed as enhanced production of diagnostic kits through public–private partnership models and industrial production reforms. Enhanced testing facility for COVID-19 will help to identify new cases. Financial stresses need long-term sustainable alternative that will avoid pay cuts and unemployment. Treatment regimen, diagnostic protocols, waste disposal guidelines should be worked upon and leading national agencies be consulted for technical support, research and development.